BEST ANSWER GETS BRAINLIEST AND 3 THANKS I NEED HELP WITH THIS PLZ THANK YOU


What is the first step to simplify the expression: [–23 – [5 · (2 – 4)]] ÷ 32


Multiply 5 times 2.

Square 3.

Subtract 5 from 2.

Subtract 4 from 2


Which values for a and b make the statement (a + 2)(b – 9) = 0 true?

a = 2, b = -9

a = -2, b = 9

a = -2, b = -9

a = 2, b = 9

What is the first step to simplify the expression: [–23 – [5 · (2 – 4)]] ÷ 32


Multiply 5 times 2.

Square 3.

Subtract 5 from 2.

Subtract 4 from 2

Respuesta :

ok so remember
order of simplification
PEMDAS
parenthaseese
exponents
multiplicaton or division whichever comes first
addition or subtraction whichever comes first

ok so remmeber work from the left to right parenthasees first and work from inside to outer parenthasees

so first one

innermost parenthasees first so
first step is 2-4
subtract 4 from 2


second one
if xy=0 then assume x and y=0 so
(a+2)(b-9)=0
a+2=0
a=-2

b-9=0
b=9

so answe ris a=-2
b=9


third questions

innermost parenthaees first
subtract 4 from 2






ok
1. subtrac 4 from 2
2. a=-2, b=9
3. subtract 4 from 2